A peptide encoded by human gene MAGE-3 and presented by HLA-A2 induces cytolytic T lymphocytes that recognize tumor cells expressing MAGE-3. - van der Bruggen, P; Bastin, J; Gajewski, T; Coulie, P; Boël, P; De Smet, C; Traversari, C; Townsend, A; Boon, T (1994)
The human MAGE-3 gene is expressed in many tumors of several histological types but it is silent in normal tissues, with the exception of testis. Antigens encoded by MAGE-3 may, therefore, be useful targets for specific anti-tumor immunization of cancer patients. We reported previously that MAGE-3 codes for an antigenic peptide recognized on a melanoma cell line by autologous cytolytic T lymphocytes (CTL) restricted by HLA-A1. Here we report that the MAGE-3 gene also codes for another antigenic peptide that is recognized by CTL restricted by HLA-A2. MAGE-3 peptides bearing consensus anchor residues for HLA-A2 were synthesized and tested for binding. T lymphocytes from normal individuals were stimulated with autologous irradiated lymphoblasts pulsed with each of three peptides that showed strong binding to HLA-A2. Peptide FLWGPRALV was able to induce CTL. We obtained CTL clones that recognized not only HLA-A2 cells pulsed with this peptide but also HLA-A2 tumor cell lines expressing the MAGE-3 gene. The proportion of melanoma tumors expressing this antigen should be approximately 32% in Caucasian populations, since 49% of individuals carry the HLA-A2 allele and 65% of melanomas express MAGE-3.